**X 1 X 3**. Answer (1 of 23):.

Source: brainly.in

**solve for x : 1/x-1/x-3=4/3 ; x is not equal to 4,3 - Brainly.in**. What must be subtracted from 4x^4-2x^3-6x^2+2x+6 so that the result is exactly divisible by 2x^2+x-1? If the polynomial.

**X 1 X 3**. The (x + 1) 3 formula is one of the important algebraic identities. It is read as x plus 1 whole cube. Its (x + 1) 3 formula is expressed as (x + 1) 3 = x 3 + 3x 2 + x + 1. How To Expand the (x + 1) 3 Formula? To expand (x + 1) 3 formula we need to multiply (x + 1) three times as shown below:.

Source: www.cuemath.com

**x+1)^3 Formula | (x+1)^3 expand Formula - What Is the (x+1)^3 Formula? Examples**. Dr. Zwerdlinger graduated from the University of Colorado School of Medicine in 1995. She works in Leadville, CO and 1 other.

What must be subtracted from 4x^4-2x^3-6x^2+2x+6 so that the result is exactly divisible by 2x^2+x-1? If the polynomial k 2 x 3 − kx 2 + 3kx -k is exactly divisible by (x-3) then the positive value of k is ____. Dr. Zwerdlinger graduated from the University of Colorado School of Medicine in 1995. She works in Leadville, CO and 1 other location and specializes in Family Medicine. Dr. Zwerdlinger. Read More. 2157 Main St Fl 1, Buffalo, NY 14214 2.76 miles. DT. Solve the quadratic equation by the formula method. x 2 + x - 2 = 0 How to factorise 3x square -6x + 2 = 0 please solve question no 25 how to factorise x^2-15x-3000 Find the quadratic polynomial whose zeros are 3 + root 5 upon 5 and 3 minus root 5 upon 5.

**X 1 X 3**. 1.) a<0 and b >0 ---> x+1 < 0 and x-3 > 0 ---> x<-1 and x>3 Not possible as no intersection of the ranges. 2.) a>0 and b <0---> x+1 > 0 and x-3 < 0 ---> x<-1 and x>3---> -1

Source: www.meritnation.com

**if x -1/x =3; then find the value of x3 -1/x3 - Maths - Polynomials - 2256228 | Meritnation.com**. Solve the quadratic equation by the formula method. x 2 + x - 2 = 0 How to factorise 3x square -6x + 2 = 0 please solve.

## x-1/x=3 Find the roots of the equations

x-1/x=3 Find the roots of the equations

**if x -1/x =3; then find the value of x3 -1/x3 - Maths - Polynomials - 2256228 | Meritnation.com**

`x-1/x = 3` ⇒ x 2 - 3x -1 = 0. On comparing this equation with ax 2 + bx + c = 0, we get. a = 1, b = -3 and c = -1. By using quadratic formula, we get `x = (-b±sqrt(b^2 - 4ac))/(2a)` `⇒ x = (3±sqrt(9+4))/2` Free math problem solver answers your algebra, geometry, trigonometry, calculus, and statistics homework questions with step-by-step explanations, just like a math tutor. powered by ROYAL JONAS FILMShttps://www.instagram.com/twenejonas/ From question x+1/x =√3x+1/x =√3Cubing on both LH S and RH S we get,(x+1/x)3 =(√3)3X 3 +(1/x3)+3(x+(1/x)) = 3√3x3 +1/x3 +3(√3) =3√3By transporting we getx3 +1/x3 +3√3−3√3 =0x3 +1/x3 =0.

**X 1 X 3**. Simplify (x-1)(x-3) Expand using the FOIL Method. Tap for more steps Apply the distributive property. Apply the distributive property. Apply the distributive property. Simplify and combine like terms. Tap for more steps Simplify each term. Tap for more steps Multiply by . Move to the left of . Rewrite as ..

Source: www.teachoo.com

**Ex 4.3, 3 (i) - Find roots of x - 1/x = 3 [Quadratic Equations]**. Simple and best practice solution for (x-1)(x-3)=0 equation. Check how easy it is, and learn it for the future. Our solution.

**X 1 X 3**. Answer (1 of 45): This is how it's done. Simple. :).

Source: www.youtube.com

**x/2-1/5=x/3+1/4` - YouTube**. `x-1/x = 3` ⇒ x 2 - 3x -1 = 0. On comparing this equation with ax 2 + bx + c = 0, we get. a = 1, b = -3 and c = -1. By using.

x - (1/x) = 3 then value of x^3 - (1/x^3) is? - Get the answer to this question and access a vast question bank that is tailored for students. Please see the explanation. Look at (x + 1)(x - 3) = 0 This means that the function is 0 at x = -1 and x = 3. Also, it means that the sign of the corresponding factor changes sign at that value of x. At values of x < -1: Both (x + 1) and (x - 3) are negative. A negative multiplied by a negative is a positive, therefore, x < -1 is one of the regions where (x + 1)(x - 3) > 0. therefore x^5+1/x^5=126-3=123. the correct answer is 123.The rest of the steps are correct. Naga Durga Devi Marisetti. 15 Points. 2 years ago. x+1/x=3 (Squaring on both sides) x^2+1/x^2+2=3^2. x^2+1/x^2=9-2=7. x+1/x=3 (cubing on both sides) x^ (1/3) - Wolfram|Alpha. Volume of a cylinder? Piece of cake. Unlock Step-by-Step. Natural Language. Math Input.

**X 1 X 3**. You can Expand \( (x-1)^3 \) through formulas and simple multiplication method. first of all, I am going to expand \( (x-1)^3 \) through the formula. \( (a-b)^3 = a^3+3ab^2-3a^2b-b^3 \).

Source: www.topperlearning.com

**x 1 x 3 find x by quadratic formula - Mathematics - TopperLearning.com | 4040u6pp**. Free math problem solver answers your algebra, geometry, trigonometry, calculus, and statistics homework questions with.

Becca M. · Ahmed Elnaiem Dec 11, 2014 Step 1 Make the right side of the equation a fraction: \displaystyle{\frac{{{3}{x}^{{2}}+{2}{x}-{1}}}{{{x}^{{2}}-{1}}}}=-\frac Solution Steps. (x+1) (x+3) ( x + 1) ( x + 3) Apply the distributive property by multiplying each term of x+1 by each term of x+3. Apply the distributive property by multiplying each term of x + 1 by each term of x + 3. x^ {2}+3x+x+3. x 2 + 3 x + x + 3. Combine 3x and x to get 4x. Combine 3 x and x to get 4 x.